2017
DOI: 10.3389/fncel.2017.00020
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α Target Genes Contribute to Retinal Neuroprotection

Abstract: Hypoxia-inducible factor (HIF) is a transcription factor that facilitates cellular adaptation to hypoxia and ischemia. Long-standing evidence suggests that one isotype of HIF, HIF-1α, is involved in the pathogenesis of various solid tumors and cardiac diseases. However, the role of HIF-1α in retina remains poorly understood. HIF-1α has been recognized as neuroprotective in cerebral ischemia in the past two decades. Additionally, an increasing number of studies has shown that HIF-1α and its target genes contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 158 publications
(166 reference statements)
6
51
0
Order By: Relevance
“…Research has increasingly shown that HIF-1α plays a critical role in regulating gene expression during the pathogenesis of retinal hypoxia/ischemia injury [45][46][47][48], which has been further confirmed in our study. Intravitreally knockdown of HIF-1α significantly alleviated retinal damage and RGCs loss (Fig.…”
Section: Inhibition Of Casp8-mediated Hif-1α Signaling Protects the Rsupporting
confidence: 86%
“…Research has increasingly shown that HIF-1α plays a critical role in regulating gene expression during the pathogenesis of retinal hypoxia/ischemia injury [45][46][47][48], which has been further confirmed in our study. Intravitreally knockdown of HIF-1α significantly alleviated retinal damage and RGCs loss (Fig.…”
Section: Inhibition Of Casp8-mediated Hif-1α Signaling Protects the Rsupporting
confidence: 86%
“…Further corroborating these findings, purified primary OPCs respond to HIFα signaling stabilizer (DMOG) and blocker (Chetomin) by activating and inactivating VEGFA, respectively. Our results are consistent with previous data showing that VEGFA is a direct transcriptional target of HIFα 4042 . By leveraging our unique in vivo genetic models of VHL/VEGFA double cKO, we unequivocally prove that VEGFA is an essential downstream molecule that couples oligodendroglial HIFα function and vascular angiogenesis in the CNS, which is different from Yuen et al, 9 who reported that VEGFA was unchanged in the CNS of oligodendroglial HIFα-stabilized mutants.…”
Section: Discussionsupporting
confidence: 94%
“…While multiple genes, proteins, and transcription factors have been identified that are associated with axon death [e.g. BAX (BCL2-associated X protein), TRX (thioredoxin), HIF-1a (hypoxia-inducible factor-1a), SNCG (g-synuclein), ATF4 (activating transcription factor 4), DDIT3 (DNA damage inducible transcript 3), and BCAT1 (branched chain amino acid transaminase 1) (Libby et al, 2005a;Soto et al, 2008;Munemasa and Kitaoka, 2013;Yasuda et al, 2014;Cheng et al, 2017), the causative genes and variants remain unknown for the majority of glaucoma cases. Identification of additional sequence variants, and associated molecular and cellular processes that modulate glaucoma endophenotypes in animals and humans can definitely provide critical insights, as well as new targets for therapeutic intervention (Chintalapudi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%